2019
DOI: 10.3857/roj.2019.00087
|View full text |Cite
|
Sign up to set email alerts
|

Chemoradiotherapy versus radiotherapy alone following induction chemotherapy for elderly patients with stage III lung cancer

Abstract: PurposeIt is unclear whether adding concurrent chemotherapy (CT) to definitive radiotherapy (RT) following induction CT is a tolerable and cost effective treatment for non-small-cell lung cancer (NSCLC) patients aged 70 years or older with comorbidities. This study evaluated the actual clinical outcomes between concurrent chemoradiotherapy (CCRT) and RT alone following induction CT or not in patients (≥70 years) in a single institution’s clinical practice.Materials and MethodsA total of 82 patients with unrese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Five publications were considered to have a high and 8 a low relevance, 52 a medium (Appendix Figure C.3, Table C.3). Low relevance was assigned due to a lack of explicit description of patient characteristics in the stage III cohort [32,50,69], or pronounced discrepancies with the standard stage III population [17,[61][62][63]85]. Most studies (n = 62) were estimated to have a medium validity.…”
Section: Resultsmentioning
confidence: 99%
“…Five publications were considered to have a high and 8 a low relevance, 52 a medium (Appendix Figure C.3, Table C.3). Low relevance was assigned due to a lack of explicit description of patient characteristics in the stage III cohort [32,50,69], or pronounced discrepancies with the standard stage III population [17,[61][62][63]85]. Most studies (n = 62) were estimated to have a medium validity.…”
Section: Resultsmentioning
confidence: 99%
“…There are no benefits from chemoradiotherapy preceded by induction chemotherapy in comparison to radiotherapy for those older than 70 years. There were no significant differences in overall survival, local recurrence rate and distant metastases while, there was a poorer tolerance and higher incidence of acute esophagitis in a more intensively treatment group (32).…”
Section: Chemoradiotherapymentioning
confidence: 73%
“…Several studies on photon radiotherapy alone for patients older than 70 years with stage ΙΙΙ LA-NSCLC reported that the median PFS and OS of radiotherapy alone were 6.8 months and 11-18.1 months, respectively [18][19][20][21]. Driessen et al reported a median OS of 5 months when patients older than 70 years with stage ΙΙΙ LA-NSCLC selected non-curative treatment [19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on photon radiotherapy alone for patients older than 70 years with stage ΙΙΙ LA-NSCLC reported that the median PFS and OS of radiotherapy alone were 6.8 months and 11–18.1 months, respectively [ 18 21 ]. Driessen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation